Proteomic Analysis of Exosome-Like Vesicles Isolated From Saliva of the Tick Haemaphysalis longicornis - Nawaz, Mohsin; Malik, Muhammad Irfan; Zhang, Houshuang; Hassan, Ibrahim A.; Cao, Jie; Zhou, Yongzhi; Hameed, Mudassar; Hussain Kuthu, Zulfiqar; Zhou, Jinlin (Frontiers in Cellular and Infection Microbiology, 2020)
Extracellular vesicles (EVs), are considered as vehicles of cellular communication. Parasites usually release EVs in their excretory-secretory products to modulate host environment. However, little is known about the secretion of EVs by ticks. In this study, we show for the first time that the tick Haemaphysalis longicornis secretes EVs in saliva that resembles exosomes. EVs were purified from pilocarpine induced saliva of partially engorged H. longicornis ticks. Electron microscopy analysis revealed the presence of exosome-like vesicles with a size of 100 nm. Proteomic analysis by LC-MS/MS identified a total of 356 proteins in tick-derived EVs. Proteome data of tick-derived EVs was validated by Western blot analysis. Immunodetection of Hsp70 and GAPDH proteins indicated that the proteomics data of tick-derived EVs were highly reliable. Bioinformatics analysis (Gene Ontology) indicated association of certain biological and molecular functions with proteins which may be helpful during tick development. Likewise, KEGG database revealed involvement of vesicular proteins in proton transport, detoxification, ECM-receptor interaction, ribosome, RNA transport, ABC transporters, and oxidative phosphorylation. The results of this study provide evidence that EVs are being secreted in tick saliva and suggest that tick saliva-derived EVs could play important roles in host-parasite relationships. Moreover, EVs could be a useful tool in development of vaccines or therapeutics against ticks.